SEBUAH DESKRIPSI AWAL TENTANG WANITA SEBAGAI OBJEK DALAM KARYA SENI FOTOGRAFI INDONESIA - Arti Wulandari (Specta: Journal of Photography, Arts, and Media, 2021)
An Initial Description of Woman as the Object of Indonesian Art Photography. S-1 Photography Study Program, FSMR, ISI Yogyakarta as an art education institution in the field of photography, founded in 1993, started to graduate students in 1998. Until now, the S-1 Photography Study Program, FSMR, ISI Yogyakarta has graduated a number of art graduates from three concentrations, namely art photography, journalism, and commercial. Among the various themes that raise issues of life that are displayed in photographic works of art, one that is interesting to discuss is about women, both raised in photographic works of art created by female photographers and male photographers who have a concern in women. This research aims to analyze women as objects in photographic works of art (a case study in the Final Project of the S-1 Photography Study Program, FSMR, ISI Yogyakarta). The methods used are data collection, data classification, and data analysis. After the data was obtained from digilib.isi.ac.id and the Library of Photography Study Program, FSMR, ISI Yogyakarta and classified according to the main concentrations of expression, journalism, and commercial, the finding showed 64 titles of the Final Project of the S-1 Photography Study Program, FSMR, ISI Yogyakarta with the object of women. The details for the three study concentrations are 19 in the field of expression photography, 11 in the field of journalistic photography, and 34 in the field of commercial photography. Further studies on the aesthetic aspects of photographic works of art, which include ideational and technical aspects, can be carried out based on these initial findings.   ABSTRAKProgram Studi S-1 Fotografi,  FSMR, ISI Yogyakarta sebagai lembaga pendidikan seni di bidang fotografi, yang didirikan pada tahun 1993 mulai meluluskan sarjana pada tahun 1998. Hingga saat ini Program Studi S-1 Fotografi,  FSMR, ISI Yogyakarta telah meluluskan sejumlah sarjana seni fotografi.  Di antara beragamnya tema yang mengangkat persoalan kehidupan yang ditampilkan dalam karya seni fotografi, salah satu yang menarik adalah tentang wanita, baik yang diangkat dalam karya seni fotografi yang dicipta oleh fotografer wanita maupun fotografer pria yang mempunyai perhatian kepada wanita. Penelitian ini akan mengkaji wanita sebagai objek dalam karya seni fotografi (studi kasus dalam Tugas Akhir Program Studi S-1 Fotografi, FSMR, ISI Yogyakarta). Metode yang akan dilakukan adalah pengumpulan data, pengklasifikasian data, dan analisis data. Setelah data diperoleh dari digilib.isi.ac.id dan Perpustakaan Program Studi Fotografi, FSMR, ISI Yogyakarta dan diklasifikasikan menurut bidang seni/ekspresi, jurnalistik, dan komersial hasilnya diperoleh 64 judul TA karya seni fotografi Tugas Akhir Program Studi S-1 Fotografi, FSMR, ISI Yogyakarta yang berobjek wanita atau perempuan. Rincian untuk ketiga bidang itu adalah 19 di bidang fotografi seni/ekspresi, 11 di bidang fotografi jurnalistik, dan 34 di bidang fotografi komersial. Kajian lebih lanjut tentang aspek estetik karya seni fotografi,  dapat dilakukan berdasarkan hasil temuan awal ini.